Contemporary art practices and knowledge production into mediation in museums for People with Alzheimer - Marta García Cano (Arteterapia)
The Contemporary art museums acting like social agent before the territory and its inhabitants is becoming an emerging idea going through the strategies of the institution. Mediator and artist/educator and the new understanding for them encourage education team works strategies to social involvement. From this point of view, an experience with people with Alzheimer and their companions in Centro de Arte de Alcobendas (Madrid) funded by DKV Seguros is introduced. The aim designed for this proposal pretend to find out evidence about the validity and new possibilities of this methodology based on contemporary art practices in the context of museums education, especially regarding health collective. We also understand the experience as social knowledge production driving in two ways. From the museum to the collective and society and the opposite. The results have been analyzed throughout a qualitative research method (implicit in artist practices) and they have displayed specific therapeutic benefits. On the other hand, from a wider point of view, some judgement and research questions have been made in order to consider the utility, efficiency and sustainability of this practices and its influence in social transformation.